Natural environmental disclosures: strategic responses by Port Moresby stock exchange entities - Brown, Alistair (Wiley Interscience, 2007)
This paper discusses the components of a simplified natural environment disclosure (NED) index that accommodates a developing country setting, and examines the level of NED in annual reports of all Port Moresby Stock Exchange (POMSoX) entities of Papua New Guinea for 2002. The results of the study found a low level of NED consistent with what Brown and Tower (2002) coin a traditional reporting model, although POMSoX entities showed a much higher level of NED than their Pacific Island Country counterparts. A number of conventional accounting predictors were put forward to explain the level of NED. None of the predictors explained aggregated NED, but some of the predictors, most notably stock exchange listing, explained some individual components of NED. The very low level of NED flies in the face of much natural environmental regulation in PNG. Clearly, POMSoX regulations, POMSoX entities and international accounting advisers need to focus on the reporting of natural environmental issues if environmental accounting is to take shape in this part of the developing world.